Types of university-industry collaboration in universities in Malaysia - Othman, Norazimah (2013)
Purpose of this study is to explore types of university-industry collaboration and the benefits generated from the collaborations. This study also explores R&D performance affected from the benefits gain< d in Universities in Malaysia. Besides that, it tries to identify the characteristics should R&D project have, in order to encourage industry to collaborate with the R&D project in Universities in Malaysia, and lastly to suggest and recommend towards increasing R&D project performance based on data analyzed Approach: The theoretical model and hypotheses in this study were tested using empirical data gathered from 85 samples of respondents that were a universities researchers through survey questionnaires and then the data being analyzed using the regression. Results: The results revealed that two types of U-I collaborations which is joint venture and contract research are the most effective U-I collaborations, while the factor of projects characteristics, barriers, and goo1 practices can attract industries attention to consider the collaboration. Conclusion: This study has explored the types of U-I collaborations in universities in Malaysia. Good practices in U-l collaborations, good characteristics, and barriers also were identified in this research. The types of collaboration were studied and the most important types were identified in this study and should be useful for universities to plan on R&D project in future.